Augmentation by cerclage wire improves fixation of vertical shear femoral neck fractures—A biomechanical analysis. Issue 10 (October 2016) - Kuan, Fa-Chuan; Yeh, Ming-Long; Hong, Chih-Kai; Chiang, Florence L.; Jou, I-Ming; Wang, Ping-Hui; Su, Wei-Ren
Abstract: Background: Femoral neck fractures in young individuals are typically vertical shear fractures. These injuries are difficult to stabilize due to a significant varus displacement force across the hip with weight bearing. The purpose of this study was to evaluate the biomechanical stability offered by the addition of an augmented wire to conventional inverted triangle triple screw fixation for stabilizing vertical shear femoral neck fracture. Methods: Sixteen medium 4th-generation synthetic composite femurs (Sawbones Pacific Research Laboratories, Vashon, WA) were divided into two groups. Vertical osteotomy was performed to mimic Pauwels III femoral neck fracture. Group A (n = 8) was fixed with three parallel 6.5-mm cannulated screws (Stryker) with washer in inverted triangle configuration. In group B (n = 8), all the screws were set using methods identical to group A, with the addition of the cerclage wire. Both groups were tested with nondestructive axial compression test at 7 and 25 ° of valgus stress, respectively. Then axial cyclic loading test with 1000 N was applied for 1000 cycles, and interfragmentary displacement was measured with Fastrak magnetic tracking system (Polhemus, Colchester, VT, USA). Finally, destructive axial compression test was conducted at 7°of valgus stress. Results: Axial stiffness showed that group B had a 66% increase (879 N/mm vs. 1461 N/mm, P < 0.01) at 7° valgus and a 46% increase (1611 N/mm vs. 2349 N/mm, P < 0.01) at 25° valgus in comparison with group A. Interfragmentary fracture displacement after cyclic loading was significantly less for group B compared with group A (0.34 vs 0.13 mm, P = 0.0016). For axial failure load, there was 42% increase in group B compared with group A (2602 N/mm vs. 3686 N/mm, P = 0.0023). Conclusions: Our study demonstrates that the addition of a cerclage wire to inverted triangle triple screws provides substantial improvement in mechanical performance regarding fixation of vertically oriented femoral neck fractures when compared with the conventional construct. Our study provides support from a mechanical analysis perspective for the reported clinical usefulness of the cerclage wire.